"What is, Becomes What is Right": A Conceptual Framework of Newcomer Legitimacy for Online Discussion Communities. Issue 4 (21st April 2015) - Gallagher, Silvia Elena; Savage, Timothy
Abstract: Online community newcomers can face challenges in community participation, acceptance and fostering member relationships. Consequently, a crucial behavioral strategy for community acceptance identified by previous research is legitimacy. However, current conceptions lack classification and structure, and have a narrow focus. A broader scope for investigating legitimacy is needed for improved theoretical and practical application. This research expands on newcomer legitimacy by classifying newcomer behavior in 4 parenting and cycling discussion communities using directed content analysis. The analysis developed a newcomer legitimacy conceptual framework with categories including geographical, contextual, cultural, testimonial, lurking and external legitimacy. This research offers a valuable contribution by classifying existing theory, developing new theory, and providing a conceptual framework to guide future studies of newcomer behavior.